Malay sayings as politeness strategies - Lim, Beng Soon (Journal of Modern Languages, 2017)
This paper will elaborate on aspects of Malay culture that form the basis for politeness strategies in Malay. An attempt will be made to link the rationale behind Malay politeness strategies to their cultural norms and values. In this paper I will present values important in Malay politeness strategies through an elaboration and analysis of the cultural values disseminated through, or are evident in Malay cultural practices, everyday life and idioms.